Editor’s Message - Verde, Linda (Operating Room Nurses Association of Canada Journal, 2025)
I love the fall season with its beautiful colours and cooler temperatures. The rhythm of the seasons brings life and growth as the years march forward, often all too quickly with the busyness of our professional lives. It is important to take time to step away from the daily grind, to nurture ourselves, and to feed our thirst for knowledge. We can help you with that as you flip through the pages of our fall issue.